2010
DOI: 10.1111/j.1553-2712.2009.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emergency Department Crowding on Analgesia in Patients with Back Pain in Two Hospitals

Abstract: Objectives: The authors assessed the association between measures of emergency department (ED) crowding and treatment with analgesia and delays to analgesia in ED patients with back pain.Methods: This was a retrospective cohort study of nonpregnant patients who presented to two EDs (an academic ED and a community ED in the same health system) from July 1, 2003, to February 28, 2007, with a chief complaint of ''back pain.'' Each patient had four validated crowding measures assigned at triage. Main outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 16 publications
1
68
0
1
Order By: Relevance
“…[1][2][3] Optimal pain management is lacking in most EDs, as many patients do not receive analgesia [3][4][5][6][7][8][9][10][11][12] and time to analgesic administration is often too long. 3,[5][6][7][8][10][11][12][13][14][15][16][17][18][19] Most health care professionals underestimate pain intensity. 20,21 In the absence of tachycardia or hypertension, we observed that ED staff tend to discredit self-assessments of severe pain when patients do not appear to be suffering.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Optimal pain management is lacking in most EDs, as many patients do not receive analgesia [3][4][5][6][7][8][9][10][11][12] and time to analgesic administration is often too long. 3,[5][6][7][8][10][11][12][13][14][15][16][17][18][19] Most health care professionals underestimate pain intensity. 20,21 In the absence of tachycardia or hypertension, we observed that ED staff tend to discredit self-assessments of severe pain when patients do not appear to be suffering.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the social context of the ED environment and the potential effect on the management of pain with a recent emphasis on effect of ED overcrowding (Bernstein et al, 2009;Duignan & Dunn, 2009;Hwang, Richardson, Sonuyi, & Morrison, 2006;Hwang et al, 2008;Pines, Shofer, Isserman, Abbuhl, & Mills, 2010;Russo, 2010;Tanabe, 1996;Tanabe & Buschmann, 1999). Of those studies located, three quantitative studies measured ED nurses' perceived barriers to general pain management (Duignan & Dunn, 2009;Tanabe, 1996;Tanabe & Buschmann, 1999), four studies examined the effect of ED crowding on quality of pain care, analgesia in patients with back pain, the management of pain in older adults with hip fracture, and patients who presented at triage with severe pain (Hwang et al, 2006;Hwang et al, 2008;Pines & Hollander, 2008;Pines et al, 2010).…”
Section: Environmental Issues and Policies In The Edmentioning
confidence: 99%
“…Of those studies located, three quantitative studies measured ED nurses' perceived barriers to general pain management (Duignan & Dunn, 2009;Tanabe, 1996;Tanabe & Buschmann, 1999), four studies examined the effect of ED crowding on quality of pain care, analgesia in patients with back pain, the management of pain in older adults with hip fracture, and patients who presented at triage with severe pain (Hwang et al, 2006;Hwang et al, 2008;Pines & Hollander, 2008;Pines et al, 2010). One qualitative study was located that identified the theme things that hinder decision-making for pediatric pain (Russo, 2010).…”
Section: Environmental Issues and Policies In The Edmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In Pines et al study, 57.0% were men with the mean ± SD age of 44 ± 17 years. 12 In Nasr-Esfahani et al study, 484 patients were admitted to the ED with the mean ± SD age of 53.8 ± 20.3 which 55.8% were men. 13 In Cha et al study, 46.3% were women and 53.7% were men and the mean age was 47 years.…”
mentioning
confidence: 99%